2007
DOI: 10.1074/jbc.m701705200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Uptake Mechanisms but Similar Intracellular Processing of Two Different Toll-like Receptor Ligand-Peptide Conjugates in Dendritic Cells

Abstract: Covalent conjugation of Toll-like receptor ligands (TLR-L) to synthetic antigenic peptides strongly improves antigen presentation in vitro and T lymphocyte priming in vivo. These molecularly well defined TLR-L-peptide conjugates, constitute an attractive vaccination modality, sharing the peptide antigen and a defined adjuvant in one single molecule. We have analyzed the intracellular trafficking and processing of two TLR-L conjugates in dendritic cells (DCs). Long synthetic peptides containing an ovalbumin cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
139
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 52 publications
(53 reference statements)
8
139
0
5
Order By: Relevance
“…Moreover, Pam3CysK4-conjugated lipopeptides activated APCs through TLR2, but the internalization of the Pam3CysK4-conjugated lipopeptide was independent of TLR2. Interestingly, both clathrin-and caveolin-mediated endocytosis were necessary for the conjugate's endocytosis (37). Additionally, the different lipid structures of glycolipids with TLR2 agonist activity were found to be cross-presented by BMDCs using different intracellular pathways, but all required TLR2 (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Pam3CysK4-conjugated lipopeptides activated APCs through TLR2, but the internalization of the Pam3CysK4-conjugated lipopeptide was independent of TLR2. Interestingly, both clathrin-and caveolin-mediated endocytosis were necessary for the conjugate's endocytosis (37). Additionally, the different lipid structures of glycolipids with TLR2 agonist activity were found to be cross-presented by BMDCs using different intracellular pathways, but all required TLR2 (40).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the incorporation of CTL epitopes into synthetic lipopeptides with TLR2 agonist activity has been shown to induce Ag-specific CD8 + T cell responses (34,37). However, there is limited information regarding the TLR2-mediated cross-priming of CTLs and its antitumor effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot exclude that R848 and CpG would boost flu subunit vaccine responses if physically linked to the HA-Ag through direct conjugation or through a delivery system. Indeed, several publications have shown that direct conjugation of TLR2, 7, and 9 agonists to the Ag increases their adjuvanticity (26,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrated that TLR ligand promoted endosomal acidification, proteasomal activity, and TAP translocation in DCs, resulting in the efficient presentation of exogenous antigen and enhancement of CTL activation [58][59][60][61]. Therefore, promotion of cross-presentation would be involved in CTL induction by vaccination with ELL.…”
Section: Discussionmentioning
confidence: 99%